2009
DOI: 10.1186/1477-7525-7-85
|View full text |Cite
|
Sign up to set email alerts
|

Associations between general self-efficacy and health-related quality of life among 12-13-year-old school children: a cross-sectional survey

Abstract: Background: While research on school children's health has mainly focused on risk factors and illness, few studies have examined aspects of health promotion. Thus, this study focuses on health promotional factors including general self-efficacy (GSE) and health-related quality of life (HRQOL). GSE refers to a global confidence in coping ability across a wide range of demanding situations, and is related to health. The purpose of this study was to examine associations between GSE and HRQOL, and associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 39 publications
3
55
0
6
Order By: Relevance
“…For example, school health services should implement interventions that aim to help children reach their goals and strengthen their self-efficacy. Previous research indicates that general self-efficacy may help increase the HRQoL of school-aged children (Kvarme, Haraldstad, Helseth, Sorum, & Natvig, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…For example, school health services should implement interventions that aim to help children reach their goals and strengthen their self-efficacy. Previous research indicates that general self-efficacy may help increase the HRQoL of school-aged children (Kvarme, Haraldstad, Helseth, Sorum, & Natvig, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The few studies that nevertheless focused on general self-ef fi cacy in children found that schoolchildren (12-14 years of age), who reported higher general self-ef fi cacy also reported lower depressive symptoms and dysfunctional thoughts (Pössel, Baldus, Horn, Groen, & Hautzinger, 2005 ) and more physical as well as emotional well-being (Kvarme, Haraldstad, Helseth, Sørum, & Natvig, 2009 ) . First interventions to promote a general sense of self-ef fi cacy were successful among schoolgirls, however not among schoolboys (Kvarme et al, 2010 ) .…”
Section: Childrenmentioning
confidence: 99%
“…Somatisering av psykiske problemer, som hodepine, magesmerter og lignende er et tegn på dårligere HRLK hos ungdom (10,15). Faktorer som mental helse, stress, selvtillit og mestring virker inn på ungdoms HRLK og bør arbeides med gjennom programmer i skolen (16)(17)(18)(19).…”
Section: Introduksjonunclassified
“…Man peker på at jenter har lavere psykososial helse og selvtillit (9,19), og forskning viser også at det er jenter som uttrykker mest somatisering av psykososiale problemer (10,15,29). Forskning på mulige årsaker til kjønnsforskjeller i HRLK peker på at kvinner synes å oppleve sterkere emosjonell intensitet enn menn.…”
Section: Introduksjonunclassified
See 1 more Smart Citation